Exposed modified asphalt waterproof coating as well as preparation method and application thereof

By adding compounded functional emulsions, ultraviolet absorbers, light stabilizers, modified glass microspheres, and nano-TiO2 to modified bitumen waterproof coatings, the problem of insufficient UV resistance in modified bitumen waterproof coatings is solved, achieving high-efficiency aging resistance, heat insulation, and flame retardant properties, making it suitable for building surfaces exposed to sunlight for extended periods.

CN119286399APending Publication Date: 2025-01-10TIANJIN YUSHEN BUILDING WATERPROOF MATERIAL

Patent Information

Application Number
CN202411341692.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing modified bitumen waterproof coatings have poor UV resistance and cannot be exposed to sunlight for extended periods, which can easily lead to coating cracking and leakage.

Method used

The formula employs a compound functional emulsion, ultraviolet absorber, and light stabilizer, and incorporates modified glass microspheres and nano-TiO2 to improve aging resistance through synergistic effects. The combination of the reflectivity of glass microspheres and the absorption capacity of nano-TiO2 enhances ultraviolet resistance.

Benefits of technology

It significantly improves the anti-aging properties of modified bitumen waterproof coatings, reduces the possibility of UV damage, and has good heat insulation, noise reduction, and flame retardant properties, making it suitable for building surfaces exposed to sunlight for extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059884250000111
    Figure BDA0005059884250000111
  • Figure BDA0005059884250000121
    Figure BDA0005059884250000121
Patent Text Reader

Abstract

The invention relates to the field of liquid coiled materials, and particularly discloses an exposed modified asphalt waterproof coating as well as a preparation method and application thereof. The modified asphalt waterproof coating is prepared from the following raw materials in parts by weight: 30-35 parts of compound functional emulsion; 25 to 30 parts of emulsified asphalt; 0.2 to 0.4 part of a defoaming agent; 0.3 to 0.5 part of a dispersant; 0.2 to 0.4 part of a multifunctional auxiliary agent; 20 to 30 parts of heavy calcium carbonate; 10 to 12 parts of glass beads; 2-4 parts of a silane coupling agent; 3-5 parts of an ultraviolet light absorber; and 2-3 parts of a light stabilizer. The exposed modified asphalt waterproof coating disclosed by the invention has relatively good aging resistance, also has good heat insulation and noise reduction performance and flame retardance, can be widely applied to building surfaces exposed to sunlight for a long time, and is relatively high in safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of liquid coiled materials, specifically, to the field of modified asphalt waterproof coatings, and more specifically, it relates to an exposed modified asphalt waterproof coating and a preparation method and application thereof. Background Art

[0002] Liquid coiled material is a polymer liquid waterproof material. After construction, it can form a waterproof layer similar to coiled material, thereby effectively preventing water penetration and having a high-strength waterproof effect. Compared with traditional waterproof coiled materials, liquid coiled materials have better adaptability and construction convenience, can be applied to surfaces of various complex shapes, and do not require open flames for construction, which improves construction safety. In addition, liquid coiled materials also have the advantages of good elasticity, high elongation, and the ability to adapt to deformation and cracking of the base layer. They can maintain the integrity of the waterproof layer and are widely used in the waterproof field of construction projects.

[0003] The main component of the liquid coil is modified asphalt waterproof coating, which not only has the characteristics of water resistance, weather resistance, and corrosion resistance of asphalt, but also improves its flexibility and wear resistance through modification, and can maintain good waterproof effect in various complex environments. However, most modified asphalt waterproof coatings currently have poor UV resistance and cannot be directly applied to the surface of buildings exposed to sunlight for a long time. If exposed to ultraviolet rays for a long time, the coating may crack, resulting in roof leakage, causing serious losses to people's lives and property. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides an exposed modified asphalt waterproof coating and a preparation method and application thereof.

[0005] In the first aspect, the present application provides an exposed modified asphalt waterproof coating, which adopts the following technical solution: An exposed modified asphalt waterproof coating, the raw materials used include the following components in parts by weight: Compound functional emulsion 30-35 parts; Emulsified asphalt 25-30 parts; Defoaming agent 0.2-0.4 parts; Dispersant 0.3-0.5 parts; Multifunctional additive 0.2-0.4 parts; Heavy calcium carbonate 20-30 parts; Glass beads 10-12 parts; Silane coupling agent 2-4 parts; 3-5 parts of ultraviolet absorber; 2-3 parts of light stabilizer; The compound functional emulsion comprises fluorine-modified acrylic emulsion and chlorinated polyethylene emulsion in a weight ratio of (5-7):(3-5).

[0006] By adopting the above technical scheme, the present application adopts a certain ratio of fluorine-modified acrylic emulsion and chlorinated polyethylene emulsion to mix and prepare a compound functional emulsion, giving full play to the synergistic effect of the two emulsions, so that the compound functional emulsion has excellent anti-aging performance, and also has a certain flame retardant effect. Adding it to the modified asphalt waterproof coating, and matching it with ultraviolet absorbers and light stabilizers, can greatly improve the aging resistance of the modified asphalt waterproof coating, which is conducive to resisting the damage of ultraviolet rays to the modified asphalt waterproof coating, and reducing the possibility of aging of the modified asphalt waterproof coating after sun exposure and rain. In addition, the present application also adds glass beads to the modified asphalt waterproof coating. The glass beads can reflect sunlight, reduce the damage of ultraviolet radiation to the modified asphalt waterproof coating, and also play a role in heat insulation and noise reduction, which greatly improves the energy saving and environmental protection of the modified asphalt waterproof coating.

[0007] Preferably, the composite functional emulsion comprises a fluorine-modified acrylic emulsion and a chlorinated polyethylene emulsion in a weight ratio of 6:4.

[0008] By adopting the above-mentioned technical scheme, the present application further optimizes the ratio between fluorine-modified acrylic emulsion and chlorinated polyethylene emulsion, promotes the synergistic anti-aging ability of the two, thereby further improving the anti-aging ability of the modified asphalt waterproof coating, and at the same time makes the modified asphalt waterproof coating have a lower production cost.

[0009] Preferably, the glass microspheres are fluorine-containing resin modified glass microspheres.

[0010] Preferably, the fluorine-containing resin modified glass microspheres are prepared by the following method: a. Mix a 0.3 mol / L NaOH solution and glass beads at 78-82°C for 1.2-1.5 hours, then filter and wash to neutrality to obtain hydroxylated glass beads; b. dispersing the hydroxylated glass microspheres in an ethanol aqueous solution, then adding γ-aminopropyltriethoxysilane, and stirring at a temperature of 80-85° C. for 1.8-2 h, then filtering, washing, drying, and sieving to obtain amino glass microspheres; c. After dispersing the amino glass microspheres in the solvent, mixing with the hexamethylene diisocyanate trimer and the solvent, and stirring at a temperature of 20-25° C. for 4-4.5 hours to obtain a dispersion of glass microspheres containing isocyanate groups; d. Mix the dispersion of glass microspheres containing isocyanate groups with a fluorine-containing resin and a solvent, and stir at a temperature of 20-25° C. for 10-12 hours, and then filter, wash, dry, and sieve to obtain fluorine-containing resin-modified glass microspheres.

[0011] Preferably, the solvent comprises xylene, ethyl acetate and butyl acetate in a weight ratio of (5-7):(6-8):(6-8).

[0012] Since glass microspheres are inorganic silicate materials, when they are directly mixed with substrates such as compound functional emulsions, the polarity difference is large, resulting in thermodynamic incompatibility and weak interface interaction, which will affect the performance of modified asphalt waterproof coatings. Therefore, by adopting the above technical solution, this application uses fluorine-containing resin to modify glass microspheres, which not only improves the dispersibility of glass microspheres in the substrate, but also enhances the interface bonding strength between it and the substrate, thereby improving the various properties of modified asphalt waterproof coatings.

[0013] Moreover, fluorine-containing resin has the advantages of excellent weather resistance and low solar heat absorption rate, and can play a synergistic role with compound functional emulsion, ultraviolet absorber, light stabilizer and other components to further improve the aging resistance and heat insulation and noise reduction effect of modified asphalt waterproof coating, reduce the damage of ultraviolet rays to modified asphalt waterproof coating, and reduce the possibility of aging of modified asphalt waterproof coating due to sun exposure and rain. In addition, the good thermal stability of fluorine-containing resin can also play a synergistic flame retardant role with compound functional emulsion, improving the flame retardant performance of modified asphalt waterproof coating.

[0014] The glass microspheres of the present application are hollow glass microspheres with a particle size of 2-3 μm and a density of 2 g / cm 3 The NCO content of the hexamethylene diisocyanate trimer of the present application is 19.6%. The fluorine-containing resin of the present application is a JF-2X type FEVE fluorine-containing resin, which has a number average molecular weight of 20,000, a hydroxyl value of 25 mgKOH / g, and a fluorine content of 25 wt%.

[0015] Preferably, the raw material further comprises 0.37-0.48 parts by weight of modified nano-TiO2, wherein the modified nano-TiO2 is nano-TiO2 with a layer of SiO2 film coated on the surface.

[0016] By adopting the above technical solution, the present application also adds a certain amount of modified nano-TiO2 to the modified asphalt waterproof coating, and uses it to play a synergistic role with components such as ultraviolet absorbers, thereby further improving the resistance of the modified asphalt waterproof coating to ultraviolet light aging. Compared with directly adding nano-TiO2, the present application coats a layer of SiO2 film on its surface, which can not only improve the dispersibility of nano-TiO2 in the substrate, but also inhibit the photocatalytic activity of nano-TiO2, thereby reducing the possibility of yellowing, powdering and even shedding of the coating, and can further improve the ultraviolet absorption capacity of nano-TiO2.

[0017] Preferably, the modified nano-TiO2 is prepared by the following method: The nano-TiO2 dispersion and the sodium hexametaphosphate solution are mixed and dispersed and heated to 90-95°C, the amount of sodium hexametaphosphate used is 0.4-0.5% of the weight of the nano-TiO2, and then the pH value of the system is adjusted to 9-10 with a 1 mol / L NaOH solution, and then a sodium silicate solution is added, and the weight ratio of sodium silicate to nano-TiO2 is (1.8-2.2):1, and then the pH value of the system is adjusted to 9.5-10.5 with a 0.1 mol / L HCl solution, and the reaction is kept warm for 0.5-1h, and then cooled, centrifuged, washed, and dried to obtain modified nano-TiO2.

[0018] By adopting the above technical scheme, the present application adopts nano-TiO2 as core material, sodium silicate as coating material, sodium hexametaphosphate as dispersant, and obtains nano-TiO2 with a layer of SiO2 film coated on the surface. Among them, the present application optimizes the addition amount of sodium hexametaphosphate, so that the nano-TiO2 can be dispersed more well, and the dispersion stability of the nano-TiO2 is improved. In addition, the present application also optimizes the weight ratio of sodium silicate and nano-TiO2, so that the SiO2 film can be well coated on the surface of the nano-TiO2. If the silicon-titanium is relatively small, the SiO2 generated by the sodium silicate is less, and the nano-TiO2 cannot be well coated. If the silicon-titanium is relatively large, the coating will be too thick, which increases the particle size of the nanoparticles, makes it easy to self-agglomerate, and affects the dispersibility of the modified nano-TiO2.

[0019] In the second aspect, the present application provides a method for preparing an exposed modified asphalt waterproof coating, which adopts the following technical scheme: A method for preparing an exposed modified asphalt waterproof coating comprises the following steps: S1. Stir the compound functional emulsion, dispersant, heavy calcium carbonate, glass beads and silane coupling agent at a speed of 250-350r / min for 35-45min; S2. Add a defoamer and a multifunctional additive to the resultant of step S1, adjust the speed to 750-850r / min and stir for 1-1.5h; S3. Adjust the rotation speed to 150-250r / min, add emulsified asphalt, ultraviolet absorber and light stabilizer to the result of step S2, and continue stirring for 10-30min to obtain a modified asphalt waterproof coating.

[0020] By adopting the above technical solution, the modified asphalt waterproof coating prepared in this application has better anti-ultraviolet aging ability, flame retardant performance, and heat insulation and noise reduction ability than the existing modified asphalt waterproof coating. At the same time, the raw materials are easily available, the preparation process is simple, the construction is convenient, safe and reliable, the overall cost is low, and it is suitable for large-scale industrial production and wide use.

[0021] Preferably, in step S1, 0.37-0.48 parts by weight of modified nano-TiO2 is also added.

[0022] In the third aspect, the application of an exposed modified asphalt waterproof coating provided by the present application adopts the following technical solution: The invention discloses an application of an exposed modified asphalt waterproof coating, which is made into a liquid coiled material and applied to waterproof buildings.

[0023] In summary, this application has the following beneficial technical effects: 1. The exposed modified asphalt waterproof coating of the present application has good aging resistance, is conducive to resisting the damage of ultraviolet rays to the modified asphalt waterproof coating, reduces the possibility of aging of the modified asphalt waterproof coating after sun exposure and rain, and also has good heat insulation and noise reduction performance and flame retardant performance, can be widely used in the surface of buildings exposed to sunlight for a long time, and has high safety; 2. The preparation method of the exposed modified asphalt waterproof coating of the present application has the characteristics of easy availability of raw materials, simple preparation process, convenient construction, safety and reliability, and low overall cost, and is suitable for large-scale industrial production and wide use. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] Unless otherwise specified, the raw materials used in this application are all commercially available products, including: Fluorine-modified acrylic emulsion, purchased from Cansen Chemical New Materials (Shenzhen) Co., Ltd., model CS-7718W, solid content of 40-42%, pH value of 6.5-8, viscosity of 40-300cp; Chlorinated polyethylene emulsion, purchased from Dongguan Xinhua New Material Technology Co., Ltd., model X-696, solid content ≥35%, viscosity 1400-1800 mPa·s, pH 8-9, chlorine content 26%; Emulsified asphalt, anionic emulsified asphalt, purchased from Anhui Boyou New Materials Co., Ltd., with a solid content of ≥55% and a viscosity of 200-400 mPa·s; The defoamer is a compound defoamer, which is composed of a metal soap defoamer and a silicone defoamer, and the weight ratio of the two is 1:1. The model of the metal soap defoamer is NOPCO NXZ, and the model of the silicone defoamer is BASF A10; The dispersant is an amine salt dispersant composed of a polymer of hydrophobically modified polyacrylic acid ammonium salt, and its model is San Nopco SN-5027; Multifunctional additive, which is a multifunctional amine additive, model AMP-95; Heavy calcium carbonate is active heavy calcium carbonate with a fineness of 800 mesh; Glass microspheres are hollow glass microspheres with a particle size of 2-3 μm and a density of 2 g / cm 3 ; Silane coupling agent, model KH-560, active ingredient content ≥ 99%; The UV absorber is a benzotriazole UV absorber, model number UV1130, and the dynamic viscosity is 7400mPa·s; the light stabilizer is a hindered amine light stabilizer, model number LQ-292, and the light transmittance is 425nm≥94%; γ-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Wuhan Shuer Biotechnology Co., Ltd.; Hexamethylene diisocyanate trimer, NCO content 19.6%; Fluorine-containing resin, model JF-2X FEVE fluorine-containing resin, purchased from Shanghai Dongfu Chemical Technology Co., Ltd., with a number average molecular weight of 20,000, a hydroxyl value of 25 mgKOH / g, and a fluorine content of 25 wt%; Sodium silicate is an instant powdered sodium silicate purchased from Jinan Deqiao Chemical Technology Co., Ltd.

[0026] Preparation Example 1 Fluorine-containing resin modified glass microspheres are prepared by the following method: a. 600 L of 0.3 mol / L NaOH solution and 20 kg of hollow glass microspheres were mixed and stirred at 78 ° C for 1.5 h, then filtered and washed with water until neutral to obtain hydroxylated glass microspheres; b. Mix the hydroxylated glass microspheres with 180 kg of ethanol and 20 kg of deionized water, and perform ultrasonic dispersion for 20 min to obtain a hydroxylated glass microsphere dispersion. Then, add 0.2 kg of γ-aminopropyltriethoxysilane to the hydroxylated glass microsphere dispersion, and stir at 80 ° C for 2 h. Then, filter and rinse with anhydrous ethanol for 3 times, and vacuum dry at 70 ° C for 12 h and then sieve to obtain amino glass microspheres. c. Add the amino glass beads to 80L of solvent (the weight ratio of xylene, ethyl acetate, and butyl acetate is 5:6:6), and ultrasonically disperse for 20 minutes to obtain an amino glass bead dispersion, and mix the amino glass bead dispersion with 0.24kg of hexamethylene diisocyanate trimer and 40L of solvent (the weight ratio of xylene, ethyl acetate, and butyl acetate is 5:8:8), and stir at a temperature of 20°C for 4.5h to obtain a glass bead dispersion containing an isocyanate group; d. Mix the glass microsphere dispersion containing isocyanate groups with 0.5 kg of JF-2X FEVE fluorine-containing resin and 40 L of solvent (the weight ratio of xylene, ethyl acetate and butyl acetate is 7:7:7), stir at 20°C for 12 h, filter, rinse with solvent 3 times, dry at 140°C for 12 h and then sieve to obtain fluorine-containing resin modified glass microspheres.

[0027] Preparation Example 2 Fluorine-containing resin modified glass microspheres are prepared by the following method: a. 600 L of 0.3 mol / L NaOH solution and 20 kg of hollow glass microspheres were mixed and stirred at 82 ° C for 1.2 h, then filtered and washed with water until neutral to obtain hydroxylated glass microspheres; b. Mix the hydroxylated glass microspheres with 180 kg of ethanol and 20 kg of deionized water, and perform ultrasonic dispersion for 20 min to obtain a hydroxylated glass microsphere dispersion. Then, add 0.2 kg of γ-aminopropyltriethoxysilane to the hydroxylated glass microsphere dispersion, and stir at 85 ° C for 1.8 h. Then, filter and rinse with anhydrous ethanol for 4 times, and vacuum dry at 70 ° C for 12 h and then sieve to obtain amino glass microspheres. c. Add the amino glass beads to 80L of solvent (the weight ratio of xylene, ethyl acetate, and butyl acetate is 5:8:6), and ultrasonically disperse for 20 minutes to obtain an amino glass bead dispersion, and mix the amino glass bead dispersion with 0.24kg of hexamethylene diisocyanate trimer and 40L of solvent (the weight ratio of xylene, ethyl acetate, and butyl acetate is 6:7:7), and stir at 25°C for 4 hours to obtain a glass bead dispersion containing isocyanate groups; d. Mix the glass microsphere dispersion containing isocyanate groups with 0.5 kg of JF-2X FEVE fluorine-containing resin and 40 L of solvent (the weight ratio of xylene, ethyl acetate and butyl acetate is 7:6:6), and stir at 25°C for 10 hours, then filter, rinse with solvent 4 times, dry at 140°C for 12 hours and sieve to obtain fluorine-containing resin modified glass microspheres.

[0028] Preparation Example 3 Modified nano-TiO2 is prepared by the following method: 1 kg of nano-TiO2 was added into deionized water to obtain a nano-TiO2 dispersion, 4 g of sodium hexametaphosphate was dissolved in water to obtain a sodium hexametaphosphate solution, the sodium hexametaphosphate solution was added into the nano-TiO2 dispersion, dispersed by high-speed mixing and heated to 90°C, and then the pH value of the system was adjusted to 9 with a 1 mol / L NaOH solution, and then a sodium silicate solution was added, the amount of sodium silicate was 1.8 kg, and then the pH value of the system was adjusted to 9.5 with a 0.1 mol / L HCl solution, and the reaction was kept warm for 0.5 h, and then cooled, centrifuged, washed, and dried at a constant temperature of 80°C for 2 h to obtain modified nano-TiO2.

[0029] Preparation Example 4 Modified nano-TiO2 is prepared by the following method: 1 kg of nano-TiO2 was added into deionized water to obtain a nano-TiO2 dispersion, 5 g of sodium hexametaphosphate was dissolved in water to obtain a sodium hexametaphosphate solution, the sodium hexametaphosphate solution was added into the nano-TiO2 dispersion, dispersed by high-speed mixing and heated to 95°C, and then the pH value of the system was adjusted to 10 with a 1 mol / L NaOH solution, and then a sodium silicate solution was added, the amount of sodium silicate was 2.2 kg, and then the pH value of the system was adjusted to 10.5 with a 0.1 mol / L HCl solution, and the reaction was kept warm for 1 hour, and then cooled, centrifuged, washed, and dried at a constant temperature of 80°C for 2 hours to obtain modified nano-TiO2.

[0030] Preparation Example 5 The difference from Preparation Example 4 is that no sodium hexametaphosphate is added, and the nano-TiO2 dispersion is directly reacted with the sodium silicate solution. The rest is the same as Preparation Example 4.

[0031] Preparation Example 6 The difference from Preparation Example 4 is that the amount of sodium hexametaphosphate used is 2 g, and the rest is the same as Preparation Example 4.

[0032] Preparation Example 7 The difference from Preparation Example 4 is that the amount of sodium hexametaphosphate used is 7 g, and the rest is the same as Preparation Example 4.

[0033] Preparation Example 8 The difference from Preparation Example 4 is that the amount of sodium silicate used is 2 kg, and the rest is the same as Preparation Example 4.

[0034] Preparation Example 9 The difference from Preparation Example 4 is that the amount of sodium silicate used is 1 kg, and the rest is the same as Preparation Example 4.

[0035] Preparation Example 10 The difference from Preparation Example 4 is that the amount of sodium silicate used is 3 kg, and the rest is the same as Preparation Example 4.

[0036] Example 1 A method for preparing an exposed modified asphalt waterproof coating comprises the following steps: S0. 15kg of fluorine-modified acrylic emulsion CS-7718W and 15kg of chlorinated polyethylene emulsion X-696 were mixed and stirred for 30min to obtain a compound functional emulsion; S1. 30kg of compound functional emulsion, 0.5kg of ammonium salt dispersant SN-5027, 30kg of active heavy calcium carbonate, 10kg of hollow glass microspheres and 4kg of silane coupling agent KH-560 were stirred at a speed of 250r / min for 45min; S2. Add 0.2kg of compound defoamer (0.1kg of metal soap defoamer NOPCO NXZ and 0.1kg of silicone defoamer A10) and 0.2kg of multifunctional amine additive AMP-95 to the resultant of step S1, adjust the speed to 750r / min and stir for 1.5h; S3. Adjust the rotation speed to 150r / min, add 30kg of anionic emulsified asphalt, 3kg of benzotriazole ultraviolet absorber UV1130 and 3kg of hindered amine light stabilizer LQ-292 to the result of step S2, continue stirring for 30min, and discharge the material to obtain a modified asphalt waterproof coating.

[0037] Example 2 A method for preparing an exposed modified asphalt waterproof coating comprises the following steps: S0. 17.5kg of fluorine-modified acrylic emulsion CS-7718W and 17.5kg of chlorinated polyethylene emulsion X-696 were mixed and stirred for 60min to obtain a composite functional emulsion; S1. 35kg of compound functional emulsion, 0.3kg of ammonium salt dispersant SN-5027, 20kg of active heavy calcium carbonate, 12kg of hollow glass microspheres and 2kg of silane coupling agent KH-560 were stirred at a speed of 350r / min for 35min; S2. Add 0.4kg of compound defoamer (0.2kg of metal soap defoamer NOPCO NXZ and 0.2kg of silicone defoamer A10) and 0.4kg of multifunctional amine additive AMP-95 to the resultant of step S1, adjust the speed to 850r / min and stir for 1h; S3. Adjust the rotation speed to 250r / min, add 25kg of anionic emulsified asphalt, 5kg of benzotriazole ultraviolet absorber UV1130 and 2kg of hindered amine light stabilizer LQ-292 to the result of step S2, continue stirring for 10min, and discharge the material to obtain a modified asphalt waterproof coating.

[0038] Example 3 A method for preparing an exposed modified asphalt waterproof coating comprises the following steps: S0. 16.25kg of fluorine-modified acrylic emulsion CS-7718W and 16.25kg of chlorinated polyethylene emulsion X-696 were mixed and stirred for 45min to obtain a compound functional emulsion; S1. 32.5kg of compound functional emulsion, 0.4kg of ammonium salt dispersant SN-5027, 25kg of active heavy calcium carbonate, 11kg of hollow glass microspheres and 3kg of silane coupling agent KH-560 were stirred at a speed of 300r / min for 40min; S2. Add 0.3kg of compound defoamer (0.15kg of metal soap defoamer NOPCO NXZ and 0.15kg of silicone defoamer A10) and 0.3kg of multifunctional amine additive AMP-95 to the resultant of step S1, adjust the speed to 800r / min and stir for 1.3h; S3. Adjust the rotation speed to 200r / min, add 27.5kg of anionic emulsified asphalt, 4kg of benzotriazole ultraviolet absorber UV1130 and 2.5kg of hindered amine light stabilizer LQ-292 to the result of step S2, continue stirring for 20min, and discharge the material to obtain a modified asphalt waterproof coating.

[0039] Example 4 A method for preparing an exposed modified asphalt waterproof coating, which is different from Example 3 in that: in step S0, the weight ratio of fluorine-modified acrylic emulsion CS-7718W and chlorinated polyethylene emulsion X-696 is 6:4, wherein the fluorine-modified acrylic emulsion CS-7718W is 19.5 kg, and the chlorinated polyethylene emulsion X-696 is 13 kg, and the rest is the same as Example 3.

[0040] Example 5 A method for preparing an exposed modified asphalt waterproof coating, which is different from Example 3 in that: in step S0, the weight ratio of fluorine-modified acrylic emulsion CS-7718W and chlorinated polyethylene emulsion X-696 is 7:3, wherein the fluorine-modified acrylic emulsion CS-7718W is 22.75 kg, and the chlorinated polyethylene emulsion X-696 is 9.75 kg, and the rest is the same as Example 3.

[0041] Example 6 A method for preparing an exposed modified asphalt waterproof coating, which is different from Example 3 in that the hollow glass microspheres in step S1 are fluorine-containing modified glass microspheres obtained in Preparation Example 1, and the rest are the same as Example 3.

[0042] Example 7 A method for preparing an exposed modified asphalt waterproof coating, which is different from Example 3 in that the hollow glass microspheres in step S1 are fluorine-containing modified glass microspheres obtained in Preparation Example 2, and the rest are the same as Example 3.

[0043] Example 8 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.37 kg of modified nano-TiO2 prepared in Preparation Example 3 is added and mixed with components such as benzotriazole ultraviolet absorber UV1130, and the rest is the same as Example 3.

[0044] Example 9 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.48 kg of modified nano-TiO2 prepared in Preparation Example 4 is added and mixed with components such as benzotriazole ultraviolet absorber UV1130, and the rest is the same as Example 3.

[0045] Example 10 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.48 kg of modified nano-TiO2 prepared in Preparation Example 5 is added and mixed with components such as benzotriazole ultraviolet absorber UV1130, and the rest is the same as Example 3.

[0046] Embodiment 11 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.48 kg of modified nano-TiO2 prepared in Preparation Example 6 is added and mixed with components such as benzotriazole ultraviolet absorber UV1130, and the rest is the same as Example 3.

[0047] Example 12 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.48 kg of modified nano-TiO2 prepared in Preparation Example 7 is added and mixed with components such as benzotriazole ultraviolet absorber UV1130, and the rest is the same as Example 3.

[0048] Example 13 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.48 kg of modified nano-TiO2 prepared in Preparation Example 8 is added and mixed with components such as benzotriazole ultraviolet absorber UV1130, and the rest is the same as Example 3.

[0049] Embodiment 14 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.48 kg of modified nano-TiO2 prepared in Preparation Example 9 is added and mixed with components such as benzotriazole ultraviolet absorber UV1130, and the rest is the same as Example 3.

[0050] Embodiment 15 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.48 kg of modified nano-TiO2 prepared in Preparation Example 10 is added and mixed with components such as benzotriazole ultraviolet absorber UV1130, and the rest is the same as Example 3.

[0051] Example 16 A method for preparing an exposed modified asphalt waterproof coating is different from that of Example 3 in that: in step S1, 0.48 kg of nano-TiO2 is added and mixed with components such as hollow glass microspheres, and the rest is the same as that of Example 3.

[0052] Comparative Example 1 The difference from Example 3 is that step S0 is removed, the compound functional emulsion in step S1 is replaced by acrylic emulsion, and the rest is the same as Example 3. Acrylic acid is purchased from Jinan Zhengyin Chemical Co., Ltd., model TL-615D, and the active ingredient content is 48%.

[0053] Comparative Example 2 The difference from Example 3 is that step S0 is removed, the compound functional emulsion in step S1 is replaced by fluorine-modified acrylic emulsion CS-7718W, and the rest is the same as Example 3.

[0054] Comparative Example 3 The difference from Example 3 is that step S0 is removed, the compound functional emulsion in step S1 is replaced by chlorinated polyethylene emulsion X-696, and the rest is the same as Example 3.

[0055] Comparative Example 4 The difference from Example 3 is that the fluorine-modified acrylic emulsion CS-7718W in step S0 is replaced by acrylic emulsion, and the rest is the same as Example 3.

[0056] Comparative Example 5 The difference from Example 3 is that the chlorinated polyethylene emulsion X-696 in step S0 is replaced by EVA emulsion, and the rest is the same as Example 3. The EVA emulsion is purchased from Nanjing Nanwei New Materials Co., Ltd., model N-512, solid content 55±1wt%, residual monomer <0.5wt%.

[0057] Comparative Example 6 The difference from Example 3 is that hollow glass microspheres are not added in step S1, and the rest is the same as Example 3.

[0058] Comparative Example 7 The difference from Example 3 is that in step S3, the benzotriazole ultraviolet absorber UV1130 and the hindered amine light stabilizer LQ-292 are not added, and the rest is the same as Example 3.

[0059] Performance Testing 1. Aging resistance: The modified asphalt waterproof coatings of the above embodiments and comparative examples were made into test pieces, and then the bonding strength and elongation at break were tested respectively according to 5.8.1 and 5.12.1 of JC / T 408-2005 "Water-emulsified asphalt waterproof coatings". The test pieces were then treated with ultraviolet light according to the method of 5.11.1.4, and the appearance was observed for bubbles, cracks, delamination, holes, etc. The bonding strength and elongation at break were tested again according to 5.8.1 and 5.12.1, and the bonding strength retention rate and elongation at break retention rate were recorded.

[0060] 2. Heat resistance: The heat resistance of the modified asphalt waterproof coatings prepared in the above embodiments and comparative examples was tested with reference to the method 5.6.1 in JC / T 408-2005 "Water-emulsified asphalt waterproof coatings", and the specimens were observed to see whether they flowed, slid, or dripped at a temperature of 130°C.

[0061] 3. Thermal conductivity: The thermal conductivity of the modified asphalt waterproof coatings prepared in the above embodiments and comparative examples was tested with reference to the method in Appendix A of 25261-2018 "Reflective Insulation Materials for Buildings".

[0062] 4. Flame retardant performance: The combustion performance grade of the modified asphalt waterproof coatings prepared in the above examples and comparative examples was tested with reference to GB 8624-2012 "Classification of Combustion Performance of Building Materials and Products".

[0063] The above performance test results are recorded in Table 1.

[0064] Table 1 Performance test results As can be seen from Table 1, the modified asphalt waterproof coatings prepared in Examples 1-3 of the present application have an adhesion strength of 0.42-0.48 MPa, an elongation at break of 712-715%, adhesion strength retention and elongation at break retention rates of more than 90%, a thermal conductivity of 0.21-0.25 W / mk, a flame retardant grade of B1, and no flowing, sliding, dripping or the like at 130°C, which is significantly higher than the requirements of various standards. This indicates that the modified asphalt waterproof coating prepared in the present application has better resistance to ultraviolet aging, good thermal insulation and noise reduction properties, and flame retardant properties, and can be widely used in building surfaces exposed to sunlight for a long time, with high safety.

[0065] The bonding strength, elongation at break, bonding strength retention rate and elongation at break retention rate of Examples 4-5 are all higher than those of Example 3, and the performance difference between Example 4 and Example 5 is small. Therefore, considering the cost reasons comprehensively, Example 4 further controls the weight ratio of fluorine-modified acrylic emulsion CS-7718W and chlorinated polyethylene emulsion X-696 to 6:4, which can give full play to the synergistic effect of the two while ensuring the handover cost, thereby improving the aging resistance of the modified asphalt waterproof coating.

[0066] The bonding strength, elongation at break, bonding strength retention rate and elongation at break retention rate of Examples 6-7 are all higher than those of Example 3, and the thermal conductivity coefficient is lower than that of Example 3. This indicates that Examples 6-7 further use fluorine-containing resin to modify the glass microbeads, which can further improve the aging resistance and thermal insulation properties of the modified asphalt waterproof coating.

[0067] The bonding strength, elongation at break, bonding strength retention rate and elongation at break retention rate of Examples 8-16 are all higher than those of Example 3, and the thermal conductivity coefficient is lower than that of Example 3, which indicates that the further addition of modified nano-TiO2 in Examples 8-15 can further improve the aging resistance and thermal insulation performance of the modified asphalt waterproof coating. And by comparing the data of Example 9 and Example 16, it can be found that compared with the direct addition of nano-TiO2, the enhancement effect of nano-TiO2 can be further improved after the modification treatment.

[0068] By comparing the data of Example 9 and Examples 10-12, it can be found that the dosage of sodium hexametaphosphate will affect the coating effect of the modified nano-TiO2, thereby affecting its reinforcing effect on the modified asphalt waterproof coating. Therefore, by further optimizing the dosage of sodium hexametaphosphate, the reinforcing effect of nano-TiO2 can be further improved.

[0069] By comparing the data of Example 9 and Examples 13-15, it can be found that the amount of sodium silicate used will affect the coating effect of the modified nano-TiO2, thereby affecting its reinforcing effect on the modified asphalt waterproof coating. Therefore, by further optimizing the weight ratio of sodium silicate and nano-TiO2, the reinforcing effect of nano-TiO2 can be further improved.

[0070] The modified asphalt waterproof coating prepared in Comparative Example 1 has an adhesion strength of 0.32 MPa, an elongation at break of 612%, an adhesion strength retention rate of 85.6%, an elongation at break retention rate of 86.1%, a thermal conductivity coefficient of 0.29 W / mk, a flame retardant grade of B2, and no flowing, sliding, dripping or the like at 110°C was detected. The results of various performance tests were worse than those of Example 3, which shows that compared with the existing acrylic emulsion, the composite functional emulsion used in this application can significantly improve the aging resistance, thermal insulation performance, heat resistance and flame retardancy of the modified asphalt waterproof coating.

[0071] The bonding strength, elongation at break, bonding strength retention rate and elongation at break retention rate of comparative examples 2-5 are all lower than those of example 3, and the thermal conductivity coefficient is higher than that of example 3. This indicates that the mixed use of fluorine-modified acrylic emulsion CS-7718W and chlorinated polyethylene emulsion X-696 in the present application can give full play to the synergistic effect of the two, thereby improving the aging resistance, thermal insulation performance, heat resistance and flame retardancy of the modified asphalt waterproof coating.

[0072] The bonding strength, elongation at break, bonding strength retention rate and elongation at break retention rate of Comparative Examples 6-7 are all lower than those of Example 3, and the thermal conductivity coefficient is higher than that of Example 3, which indicates that not adding hollow glass microspheres, benzotriazole ultraviolet absorber UV1130 or hindered amine light stabilizer LQ-292 will significantly affect the anti-ultraviolet aging ability and thermal insulation properties of the modified asphalt waterproof coating.

[0073] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An exposed modified asphalt waterproof coating, characterized in that: The raw materials used include the following components in parts by weight: Compound functional emulsion 30-35 parts; Emulsified asphalt 25-30 parts; Defoaming agent 0.2-0.4 parts; Dispersant 0.3-0.5 parts; Multifunctional additive 0.2-0.4 parts; Heavy calcium carbonate 20-30 parts; Glass beads 10-12 parts; Silane coupling agent 2-4 parts; 3-5 parts of ultraviolet absorber; 2-3 parts of light stabilizer; The compound functional emulsion comprises a fluorine-modified acrylic emulsion and a chlorinated polyethylene emulsion in a weight ratio of (5-7):(3-5).

2. The exposed modified asphalt waterproof coating according to claim 1, characterized in that: The compound functional emulsion comprises fluorine-modified acrylic emulsion and chlorinated polyethylene emulsion in a weight ratio of 6:

4.

3. The exposed modified asphalt waterproof coating according to claim 1, characterized in that: The glass microspheres are fluorine-containing resin modified glass microspheres.

4. The exposed modified asphalt waterproof coating according to claim 3, characterized in that: The fluorine-containing resin modified glass microspheres are prepared by the following method: a. Mix a 0.3 mol / L NaOH solution and glass beads at 78-82°C for 1.2-1.5 hours, then filter and wash to neutrality to obtain hydroxylated glass beads; b. dispersing the hydroxylated glass microspheres in an ethanol aqueous solution, then adding γ-aminopropyltriethoxysilane, and stirring at a temperature of 80-85° C. for 1.8-2 h, then filtering, washing, drying, and sieving to obtain amino glass microspheres; c. After dispersing the amino glass microspheres in the solvent, mixing with the hexamethylene diisocyanate trimer and the solvent, and stirring at a temperature of 20-25° C. for 4-4.5 hours to obtain a dispersion of glass microspheres containing isocyanate groups; d. Mix the dispersion of glass microspheres containing isocyanate groups with a fluorine-containing resin and a solvent, and stir at a temperature of 20-25° C. for 10-12 hours, and then filter, wash, dry, and sieve to obtain fluorine-containing resin-modified glass microspheres.

5. The exposed modified asphalt waterproof coating according to claim 4, characterized in that: The solvent includes xylene, ethyl acetate and butyl acetate in a weight ratio of (5-7):(6-8):(6-8).

6. The exposed modified asphalt waterproof coating according to claim 1, characterized in that: The raw materials also include 0.37-0.48 parts by weight of modified nano-TiO2, wherein the modified nano-TiO2 is nano-TiO2 with a layer of SiO2 film coated on the surface.

7. The exposed modified asphalt waterproof coating according to claim 6, characterized in that: The modified nano-TiO2 is prepared by the following method: The nano-TiO2 dispersion and the sodium hexametaphosphate solution are mixed and dispersed and heated to 90-95°C, the amount of sodium hexametaphosphate used is 0.4-0.5% of the weight of the nano-TiO2, and then the pH value of the system is adjusted to 9-10 with a 1 mol / L NaOH solution, and then sodium silicate solution is added, and the weight ratio of sodium silicate to nano-TiO2 is (1.8-2.2):1, and then the pH value of the system is adjusted to 9.5-10.5 with a 0.1 mol / L HCl solution, and the reaction is kept warm for 0.5-1h, and then cooled, centrifuged, washed, and dried to obtain modified nano-TiO2.

8. A method for preparing the exposed modified asphalt waterproof coating according to claim 1, characterized in that: The following steps are involved: S1. Stir the compound functional emulsion, dispersant, heavy calcium carbonate, glass beads and silane coupling agent at a speed of 250-350r / min for 35-45min; S2. Add a defoamer and a multifunctional additive to the resultant of step S1, adjust the speed to 750-850r / min and stir for 1-1.5h; S3. Adjust the rotation speed to 150-250r / min, add emulsified asphalt, ultraviolet absorber and light stabilizer to the result of step S2, and continue stirring for 10-30min to obtain a modified asphalt waterproof coating.

9. The method for preparing an exposed modified asphalt waterproof coating according to claim 8, characterized in that: In the step S1, 0.37-0.48 parts by weight of modified nano-TiO2 is also added.

10. An application of the exposed modified asphalt waterproof coating according to claim 1, characterized in that: The exposed modified asphalt waterproof coating is made into a liquid roll material and used in waterproof buildings.

Citation Information

Patent Citations

  • Asphalt rubber waterproof coating material

    CN102936460A

  • Preparation method of modified hollow glass beads grafted with fluorine-containing resin on surfaces

    CN109824941A

Cited By

  • Flame-retardant exposed liquid coiled material as well as preparation method and application thereof

    CN121718261A